INDEKS KEPUASAN INFRASTRUKTUR KABUPATEN INDRAGIRI HILIR TAHUN 2022 - Alfassa, Achmad Isya; Alfa, Akbar; Susanto, Bayu Fajar; Rosmiar, Rosmiar (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2023)
Based on the Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Surveys for Public Service Organizing Units and Regional Medium Term Development Plan Documents (RPJMD) for Indragiri Hilir Regency for 2018-2023 which have been stipulated in Regional Regulation Number 10 In 2019, placing infrastructure and a sense of security as a development mission in an effort to achieve the vision of Indragiri Hilir Regency